Transformation of Mourning and Melancholia into Revenge in the Novel Second Life Ranker: A Psychoanalytic Study Using Sigmund Freud's Theory - Arief Ahsan Hamami (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2026)
The study of trauma and loss in literary works is important to understand the psychological dynamics experienced by the characters. This study will analyse the transformation of Cha Yeon-Woo’s loss in the novel Second Life Ranker, culminating in revenge. This study will use Sigmund Freud’s psychoanalytic framework of Mourning and Melancholia because this theory can explain the relationship among melancholia, loss, and self-aggression. In the novel Second Life Ranker, there is a double loss: a mother and her twin sister. This causes grief that develops into a pathological melancholy condition. This is characterised by a libido originating from the outside world and aggression directed at oneself. Thus, causing a failure to complete the mourning process adaptively. The purpose of this study is to address two main focuses:  the form of trauma experienced by Cha Yeon-woo according to Freud's Mourning and Melancholia theory, and how the trauma is transformed into revenge and reconstructs her identity through the internalisation of the lost object. Unlike conventional psychoanalytic studies that often focus on classical literature, this research fills a gap in the literature by applying Freud's theory to the popular web novel genre that has a distinctive narrative structure such as time regression. To examine this, research uses a qualitative approach with content analysis techniques through the following steps: narrative identification, data coding based on Freud's melancholia symptoms, and psychoanalytic interpretation of aggression transformation. Through reading and note taking, this study identifies narratives that contain symptoms of mourning and melancholia, as well as the shift from grief to revenge. Meanwhile, secondary data in the form of Freud's psychoanalytic concepts of mourning and melancholia will serve as an interpretative basis. The results of this research analysis show Cha Yeon-woo's failure to complete the work of mourning. As a result, he causes his brother’s shadow to fall into the ego. So that the loss is not only felt, but becomes the lost figure to take revenge. This transformation triggers aggression that was originally directed at himself, becoming revenge. This study confirms that the grief and melancholy he experienced functioned as a source of psychic energy to avenge his twin brother